Perbandingan Antara C++ dan Java dalam Pengelolaan Sumber - Subandijo Subandijo (Bina Nusantara University, 2012)
This article contains a descriptive comparison of four features between C++ and Java. The first feature discusses about memory management that focuses on exception safety. The second compares the C++ destructor to Java finalizer. Third feature discusses about Java finally block. The forth is about C++ and Java implementation in order to access a data structure.